A Descriptive Quantitative Study of Students’ Anxiety in Reading and Writing in Learning English at the Eighth Grade of Mts Hadharatul Islamiyah Sipispis - Nadia Syahfira Purba (JADEs Journal of Academia in English Education, 2021)
This study was about students’ anxiety in reading and writing in learning English at the eighth grade of Mts Hadharatul Islamiyah Sipispis. In this research, the researcher used quantitative descriptive method. This study is aimed to find out the students’ anxiety level in reading and writing in learning English. The data was collected by using questionnaire with two aspects includes reading and writing. In this study, the researcher found that the students’ anxiety in reading are categorized in low anxiety level there are 6 students (22%), students who categorized in medium anxiety there are 10 students (37%), and the high anxiety level are 11 students (41%). While in writing anxiety in this study shows that the students categorized in low anxiety level are 4 students (15%), in medium anxiety category are 13% students (48%), and the high anxiety category are 10 students (37%). It can be concluded the students’ anxiety level in reading English at the eighth grade of MTs Hadharatul Islamiyah Sipispis is categorized in the high anxiety level. Whereas students’ level anxiety in writing in categorized medium anxiety level.